Characterization of the anisotropic conductive behavior of a copper paste for structural electronics - Ihssan Hendi; Tanguy Lacondemine; Gaétan Schneider; Manuel Fendler (Journal of Science: Advanced Materials and Devices, 2022)
There is a growing interest in structural electronics due to their ability to produce 3D electrically functionalized objects that are aimed towards sensors and Human–Machine interfaces. One approach for structural electronics is Paste Extrusion Modeling (PEM), which can instrument 3D complex objects. This technique was used in this article to extrude an insulator copper paste on various substrates. The extrusion was followed by a laser treatment that renders the paste anisotropically conductive only on the upper 30 μm of the total thickness of the applied layer. The electrical resistivity obtained after this operation was measured at 6.10−7 Ω m, which was typically found in interconnections. The raw composition of the paste, as well as the laser impact, were characterized through FTIR, Raman spectroscopy and EDS. This process opens the possibility of integrating electronics onto metallic objects thanks to its anisotropic superficial behavior.